Development Composite Metal-Ceramic Hybrids and Polymer Foam Composites Reinforced TKKS Fiber with Variations Al2O3 Concentration for Enhancement Mobility and Protection Armored Vehicle - Wulandari, Viviq Ardita; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
Armored vehicles require materials that can provide high protection from ballistic and explosive threats, and have a light weight to increase mobility. This study aims to develop metal-ceramic hybrid composites and polymer foam composites reinforced with OPEFB (Oil Palm Empty Fruit Bunches) fibers with varying concentrations of Al2O3 ( Aluminum Oxide). This combination was tested to assess mechanical strength, ballistic resistance, and energy absorption capabilities from impacts and shock waves. The results showed that the composite using a 10% Al2O3 concentration variation provided the best balance between strength and light weight. The use of these two types of composites is expected to increase the mobility and protection of armored vehicles.